O romantismo dos filmes: o impacto na percepção da síndrome de burnout e seu significado para futuros profissionais de administração - Gomes, Fernando Rodrigues Nascimento (Brasil, 2024)
A Burnout Syndrome emerges as a mental disorder triggered by excessive work, compromising the physical and mental health of the individual. The theoretical framework addresses various aspects of this syndrome, including emotional exhaustion, depersonalization, and professional dissatisfaction, examining its impacts on both employees and organizations. The main objective of the research is to analyze whether movies romanticize Burnout Syndrome and the impact of this representation on future Management professionals. To achieve this, a quantitative methodological approach was adopted, using questionnaires administered to students in the UFAM administration course. The results provide a synthesis of students' perceptions regarding Burnout portrayed in films. In summary, the study emphasizes the need to raise awareness among future professionals about the real negative effects of Burnout, countering the romanticization present in cinematic productions, with the aim of preserving the physical and mental health of individuals in the workplace.